Does employee ownership increase corporate social disclosure? The impact of labor investment inefficiency - Depoers, Florence; Jérôme, Tiphaine (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
This study examines the association between non-executive employee ownership and corporate social disclosure. Drawing on a sample of European listed firms, we estimate fixed effects panel regressions and find a positive association between non-executive employee ownership and corporate social disclosure. In line with agency theory, this finding suggests that employee-shareholders favor social disclosure to preserve their social and financial interests in the firm they work for. Our analysis further shows that this relationship is less pronounced in case of labor investment inefficiency. Overall, our findings support a cost-benefit view of corporate social disclosure and underscore the ambivalent role non-executive employee ownership may play in corporate transparency.